2009
DOI: 10.2514/1.40764
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Dynamic Modeling: Data Information Requirements and Flight-Test Results

Abstract: Practical aspects of identifying dynamic models for aircraft in real time were studied. Topics included the formulation of an equation-error method in the frequency domain to estimate nondimensional stability and control derivatives in real time, data information content for accurate modeling results, speed of convergence, and data information management techniques such as data forgetting, incorporating prior information, and optimized excitation. Real-time dynamic modeling was applied to simulation data and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 16 publications
(48 reference statements)
0
40
0
Order By: Relevance
“…Despite all of this, note here that many LOC incidents also occur when the aircraft appears to be in a nominal state, hence making the work discussed in this paper relevant even without the existence of on-line system identification procedures. In addition, some recent research [14] has shown that pilot inputs during a normal task can be effective at near real-time system identification and this may be an approach that is relevant to this task.…”
Section: A Modeling the Aircraft As A Command-driven Systemmentioning
confidence: 99%
“…Despite all of this, note here that many LOC incidents also occur when the aircraft appears to be in a nominal state, hence making the work discussed in this paper relevant even without the existence of on-line system identification procedures. In addition, some recent research [14] has shown that pilot inputs during a normal task can be effective at near real-time system identification and this may be an approach that is relevant to this task.…”
Section: A Modeling the Aircraft As A Command-driven Systemmentioning
confidence: 99%
“…In past work on fighter aircraft short-period modeling, frequency spacing of 0.04 Hz on an interval of approximately [0.1-2] Hz was found to be adequate [3][4][5][6][7] . Finer frequency spacing requires slightly more computation, but was found to have little effect on the results.…”
Section: Recursive Fourier Transformmentioning
confidence: 99%
“…A number of aerodynamic model identi¦cation methods in the context of faults/failures have been proposed in the literature, like the use of indicial functions for unsteady aerodynamic e¨ects [1], real-time identi¦cation in the frequency domain [2,3], and modi¦ed sequential least squares [4]. These publications demonstrate speci¦c advantages for each identi¦cation method.…”
Section: Introductionmentioning
confidence: 99%